The Level of Musculoskeletal Fitness of Male Pupils (9-11) Years in a Sample of Algerian Primary School Children - Mohamed KADDOUR; Ladjel GUERRACH; Mohammed MEHIDI; Abderahmane BENGUENAB (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
This study aimed to identify the level of musculoskeletal fitness of male students 9-11 For this purpose, the researchers used the descriptive method on a randomly selected sample of 750 pupils from the primary education stage in schools in the state of Oran. For the purpose of this study, the researchers used three tests, namely the basketball throwing test from a long sitting position to measure muscular strength, the sitting test from the knees with bent knees 60 seconds to measure muscular endurance, and the trunk forward flexion test from a standing position on the box to measure flexibility. After analysing the obtained results, the researchers concluded that the level of musculoskeletal fitness components was low, and this decrease was not equal in all musculoskeletal fitness components, as the decrease in muscular endurance, flexibility, and muscular strength component was better compared to previous studies. In addition, there were statistically significant differences in the musculoskeletal fitness components according to the age variable, in favour of the age group 9 years in the flexibility variable, in favour of the age group 10 years in the (muscular endurance) variable and in favour of the age group 11 years in the muscular strength variable.